2008
DOI: 10.1016/j.jnutbio.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-Diindolylmethane stimulates murine immune function in vitro and in vivo

Abstract: 3,3'-Diindolylmethane (DIM), a major condensation product of indole-3-carbinol, exhibits chemopreventive properties in animal models of cancer. Recent studies have shown that DIM stimulates interferon-gamma (IFN-gamma) production and potentiates the IFN-gamma signaling pathway in human breast cancer cells via a mechanism that includes increased expression of the IFN-gamma receptor. The goal of this study was to test the hypothesis that DIM modulates the murine immune function. Specifically, the effects of DIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 73 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…Our study identified a further important mode of action for the intriguing dietary component DIM that induces mitochondria-dependent PCD, because the effects seen from treatment with DIM are a consequence of its inhibition of the mitochondrial F0F1-ATP synthase in protozoan parasite L. donovani. The upstream events of generation of ROS are different from those in other mechanistic pathways induced by DIM in different cell lines (Xue et al, 2008). Mitochondrial membrane depolarization and ROS formation play significant roles in modulating the response of the parasite to DIM.…”
Section: Discussionmentioning
confidence: 93%
“…Our study identified a further important mode of action for the intriguing dietary component DIM that induces mitochondria-dependent PCD, because the effects seen from treatment with DIM are a consequence of its inhibition of the mitochondrial F0F1-ATP synthase in protozoan parasite L. donovani. The upstream events of generation of ROS are different from those in other mechanistic pathways induced by DIM in different cell lines (Xue et al, 2008). Mitochondrial membrane depolarization and ROS formation play significant roles in modulating the response of the parasite to DIM.…”
Section: Discussionmentioning
confidence: 93%
“…DIM is in clinical trials as a treatment for numerous forms of cancer because of its safety at high doses and its promising anti-tumor effect in vitro and in vivo (26,27). It is also being investigated as a potential treatment for a variety of viral and antibiotic-resistant bacterial infections, because of its immunomodulatory effects (28,29). The reported cellular effects of DIM are numerous (30), including cell cycle regulation, apoptosis induction, nuclear receptor-mediated gene transcriptional changes, induction of various drug-metabolizing cytochrome P450 enzymes, estrogen metabolism changes resulting in an increase in anticarcinogenic 2-hydroxylation of estrogen, inhibition of mitochondrial H ϩ -ATP synthase resulting in induction of p21…”
mentioning
confidence: 99%
“…Chemistry DIM (1), its derivatives (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and isomers of DIM [2,2Ј-DIM (22) and 2,3Ј-DIM (25)] were synthesized using the methods reported by Nagarajan and Perumal 11) and usual organic synthetic methods as shown in Charts 1 and 2. Briefly, DIM (1) and its derivatives (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were obtained by the reaction of indole or methylindole with various aldehydes or ketones (Chart 1).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, DIM (1) and its derivatives (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were obtained by the reaction of indole or methylindole with various aldehydes or ketones (Chart 1). Bis(1-benzenesulfonyl-1H-indol-2-yl)methanol (20) and (1-benzenesulfonyl-1H-indol-2-yl)(1-benzenesulfonyl-1H-indol-3-yl)methanol (24) was obtained by the reaction of 2-(19) or 3-formyl-1-benzenesulfonyl-1H-indole (23) with 1-benzenesulfonyl-1H-indole (18), followed by reduction and desulfonylation to give 2,2Ј-DIM (22) or 2,3Ј-DIM (25) (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation